Intencionalidades em conflito: um estudo das práticas educativas de ONGs - Santos, Karine dos (Universidade do Vale do Rio dos Sinos, 2015)
In Brazil, the national projection of non-governmental organizations (NGOs) was a phenomenon of the 1990s and happened in tune with a broader setting of implementation of a new societal project. Usually, NGOs are organizations that promote education practices aimed at different audiences who are recognized by common sense as socially vulnerable. Amid the advent of educational practices and the contradictions of their interventions, some social tensioning lead the NGOs to minimize the effects of their results. The proposed study aimed to shed a light on the contradictions between the educational objectives and practices developed by three NGOs that work with social assistance policy programs in São Leopoldo, Rio Grande do Sul. This thesis is grounded on principles of critical theory and popular education. The methodological framework used was participant observation, having as its main principle the manifestation of daily interaction. During this study, it was not only important to monitor the NGOs practices from the inside, but also to listen to the target audience’s opinion through interviews with the community. It could be verified that these educational practices respond in a nuclear way, i.e., they are restricted to the scope of each assisted individual, favoring the construction of individualized instruments. Therefore, it can be assumed that, within a collective scope, they do not represent the social change that these individuals aim because they do not provoke changes in the social space of the assisted population. Consequently, we can assume that there is a tendency for an alignment, either conscious or unconscious, with a neoliberal project that reproduces the social, economic and political inequalities inherent to the capitalist mode of production, contributing to a maintenance of the status quo. Finally, we consider that the social organizations have multiple intentions, which place their practices in a foggy field where projects that range from alienation to emancipation are disputed. This study aims to collaborate with the construction of perceptions about the current model of social intervention and, from that point on, to contribute to the improvement of the proposed practices in spaces such as the ones analyzed here.
Keywords: Educação social; ONGs; Campo social; Prática educativa; Comunidade; Social education; NGOs; Social field; Educational practice; Community; ACCNPQ::Ciências Humanas::Educação